2012
DOI: 10.4040/jkan.2012.42.4.466
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Eating Behavior in Elders with Dementia residing in Long-Term Care Facilities

Abstract: Purpose: The purpose of this study was to explore characteristics of eating behavior according to level of functional status of elders with dementia (EWD), and to examine feeding time, change in food intake and body mass index (BMI) according to eating behavior. Methods: Participants were 149 EWD residing in long-term care facilities located in Seoul or Gyeonggi province and evaluated using the Mini-Mental State Exam-Korean version, Korean version-Activities of Daily Living, and Eating Behavior Scale (EBS). Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…A classification score of more than 12 points indicates mild dependence, 6–11 points indicate moderate dependence, and less than 5 points indicate severe dependence. 32 Nurses trained to use the Eating Behavior Scale measured all resident participants. In their study, Tully et al 31 found the reliability between inspectors was 0.959.…”
Section: Methodsmentioning
confidence: 99%
“…A classification score of more than 12 points indicates mild dependence, 6–11 points indicate moderate dependence, and less than 5 points indicate severe dependence. 32 Nurses trained to use the Eating Behavior Scale measured all resident participants. In their study, Tully et al 31 found the reliability between inspectors was 0.959.…”
Section: Methodsmentioning
confidence: 99%
“…In accordance to our findings, more than half of the residents (56.7%) were in need of partial or total help in feeding: specifically, two patients out of ten required complete assistance by NH carers while around four patients out of ten required partial assistance. The feeding dependence that emerged is high and seems to be unique compared to that documented at the international levels, ranging from 14.6% [16] to 54.4% [18]. As a consequence of this high prevalence specific policies are required.…”
Section: Feeding-dependence Prevalence and Policy Implicationsmentioning
confidence: 99%
“…In Spain, among 3,921 residents living in 86 NHs, 373 residents in 23 NHs were selected and 60 (17.3%) were diagnosed with dysphagia and 50 (13.4%) with feeding difficulties [17]. In contrast, in 149 residents with dementia and living in long-term care facilities located in Seoul, 54.4% were in need of moderate or total assistance while eating [18]. In New Zealand, Boyd and colleagues [19], in their multiple cross-sectional study design evaluating functional decline in NH residents over 20 years, reported that the proportion of those highly dependent increased from 16% (1988) to 21% (2008); specifically, those residents requiring assistance in feeding were 35% and 25%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…이 정•류세앙 을 말한다 [5]. 또한 [4,15,16], 일상생활수행능력 [4,16,17], 체질량 지수(Body Mass Index, BMI) [15], 식사 장소 및 식이 형태 [17], 식사를 지원하는 간호제공자와의 상호작용 [8]…”
unclassified